EU regional policy between integration, regional convergence and economic growth - Lammers, Konrad (Raumforschung und Raumordnung | Spatial Research and Planning, 2007)
EU regional policy — as it exists today — was established in the course of the southern enlargement, the completion of the internal market and the introduction of the monetary union. It had been expected that poor and peripheral countries and regions could hardly draw benefits from these steps of EU integration or less than those which were already rich and located in the core of the community. Contrary to these expectations the poor countries and regions were able to catch up, in most cases considerably. It is true that presumably EU regional policy has contributed to their catching-up processes. But decisive for these processes have been the market forces which were the result of EU integration and the economic policy within the catching-up countries. Economic growth in the EU has probably not been stimulated by regional policy. Also in the current period regional policy will presumably not contribute positively to economic growth in the EU.